2021
DOI: 10.1186/s12889-021-10207-y
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparity and the risk of contracting COVID-19 in South Korea: an NHIS-COVID-19 database cohort study

Abstract: Background The relationship between socioeconomic status and the risk of contracting coronavirus disease (COVID-19) remains controversial. We aimed to investigate whether socioeconomic status affected the risk of contracting COVID-19 in the South Korean population. Methods The NHIS-COVID-19 database cohort was used in this population-based study. We collected the data of COVID-19 patients who were diagnosed between January 1, 2020 and June 4, 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 27 publications
9
29
0
1
Order By: Relevance
“…These factors could be related to employment in industries that do not allow work from home options, for example taxi services or warehouse workers, or related to employment in areas that have already experienced outbreaks, such as the meat-packing plants in Brooks. While it does not evaluate mortality from COVID-19, this finding from Alberta is consistent with those from other locales worldwide ( 8 11 ).…”
Section: Discussionsupporting
confidence: 82%
“…These factors could be related to employment in industries that do not allow work from home options, for example taxi services or warehouse workers, or related to employment in areas that have already experienced outbreaks, such as the meat-packing plants in Brooks. While it does not evaluate mortality from COVID-19, this finding from Alberta is consistent with those from other locales worldwide ( 8 11 ).…”
Section: Discussionsupporting
confidence: 82%
“…This is likely to be explained by the effect of socioeconomic status. Oh et al found that lower socioeconomic status was associated with a higher risk of contracting COVID-19 in South Korea especially in the older population [14] [15]. Comorbidity profiles and dialysis modality were comparable in our general dialysis population [16].…”
Section: Discussionsupporting
confidence: 56%
“…23 A study from Brazil reported that those with low education attainment were more likely to die from COVID-19 (OR 1.13, CI 1.07-1.19). 24 Increased deaths among the poor and low educational status patients has also been reported in recent studies from USA, 25 South Korea, 26 and African countries. 27 An epidemiological study in Santiago, Chile report a strong association between socioeconomic status and mortality, measured either by COVID-19 attributed deaths or excess deaths with greater caser-fatality rates in the young people in deprived localities.…”
Section: Discussionmentioning
confidence: 77%